2009
DOI: 10.1021/es803176k
|View full text |Cite
|
Sign up to set email alerts
|

Particle Induced Toxicity in Relation to Transition Metal and Polycyclic Aromatic Hydrocarbon Contents

Abstract: Exposure to ambient particulate matter (PM) is statistically significantly associated with morbidity and mortality. The objectives of this study were (a) to investigate in vivo pulmonary and systemic cytotoxicity and inflammatory activity in compromised animals exposed to PM and (b) to investigate the relationships of the outcomes to the chemical compositions of particular polycyclic aromatic hydrocarbons (PAH) and transition metals in the PM. The PM samples were collected in European cities representing contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 38 publications
6
43
0
2
Order By: Relevance
“…The estimated percentages for PM 2.5 were 71.9, 72.0, 65.7, and 72.3% for Joss-C (Na), Joss-MA (Al), Joss-V (Pb), and Joss-C (Cu), respectively. Taking into account, the emphasis on the health-related effects caused by the inhalation of ambient air particles containing metallic elements (Gerlofs-Nijland et al 2009), these high percentages of small particles are rather alarming. The Waste Incinerator Heavy Metal Air Pollutant Emissions Standards has already stressed the importance of controlling the emission of Pb, Cd, and Hg, owing to their toxic effect on human health.…”
Section: Metallic Element Distribution In the Original Joss Paper Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimated percentages for PM 2.5 were 71.9, 72.0, 65.7, and 72.3% for Joss-C (Na), Joss-MA (Al), Joss-V (Pb), and Joss-C (Cu), respectively. Taking into account, the emphasis on the health-related effects caused by the inhalation of ambient air particles containing metallic elements (Gerlofs-Nijland et al 2009), these high percentages of small particles are rather alarming. The Waste Incinerator Heavy Metal Air Pollutant Emissions Standards has already stressed the importance of controlling the emission of Pb, Cd, and Hg, owing to their toxic effect on human health.…”
Section: Metallic Element Distribution In the Original Joss Paper Andmentioning
confidence: 99%
“…This is because the implications of the inhalation of ambient air particles containing metallic elements on health have been reported (Gerlofs-Nijland et al 2009). The metallic elements in suspended particles generated by incense burning have been widely investigated by Fang et al (2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, fine particulate Zn has been correlated with emergency department visits in Spokane, WA [3]. Particulate transition metals have also been correlated with increasing toxicity biomarkers and shown to stimulate production of reactive oxygen species [4]. Additionally, particulate metals can be used to identify sources and develop control strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al (2011) collected airborne PM with a five-stage airborne PM sampler and reported that PAHs was unimodal distributed among the five particle sizes while the stage in the smallest particle size had the highest concentrations of PAHs. There are also numbers of works devoted to the risk assessment of PAHs associated with airborne PM (Gerlofs-Nijland et al 2009;Jiang et al 2014;Li et al 2014;Pongpiachan et al 2015). The establishment and development of benzo[a]pyrene equivalent concentration (BaP eq ) along with toxic equivalence factors (TEFs) have contributed to the recognition of the carcinogenic properties of PAHs (Zhu et al 2014;Gao et al 2015).…”
mentioning
confidence: 99%